Study on the safety and efficacy of HIFU in the treatment of VaIN - Susu Wu; Xiang Li; Dabao Xu; Mingzhu Ye (International Journal of Hyperthermia)
Purpose This study aimed to investigate the safety and efficacy of High-Intensity Focused Ultrasound (HIFU) treatment for vaginal intraepithelial neoplasia(VaIN).Methods Retrospective analysis was conducted on clinical, pathological, and follow-up data of 43 patients who underwent HIFU treatment for VaIN at Xiangya Third Hospital of Central South University between January 2018 and December 2022. The preliminary efficacy and safety of HIFU in treating VaIN were discussed.Results The 36 patients were analyzed, and the average age was 50.09 ± 12.06 years, including 24 patients with VaIN I and 12 patients with VaIN II. Five cases had a history of hysterectomy (4 due to cervical lesions, 1 due to hysteromyoma), and 2 cases had conization of cervical intraepithelial lesions (CIN). All 36 cases were complicated by human papillomavirus (HPV) infection, with 3 cases also having grade I-II CIN and undergoing cervical HIFU treatment. All patients successfully completed the HIFU treatment, with an average treatment time of 5.99 ± 1.25 min, treatment power of 3.5 W, and average total treatment dose of 1118.99 ± 316.20 J. Patients tolerated the treatment well, experiencing only slight pain with VAS score of 3. There was a mild postoperative burning sensation, which resolved within approximately 10-20 min. After 6 follow-up visits, 33 patients (91.66%) achieved cure, 1 patient (2.77%) showed persistence, 2 patients (5.55%) exhibited progression, and 27 patients (75%) tested negative for HPV. At 12 months of follow-up, the results were consistent with those of 6 months. No complications occurred during the procedure and the follow-up period.Conclusion HIFU is a safe and effective treatment for VaIN. However, this study had a small sample size, a relatively short follow-up period, and lacked a control group, requiring further investigation.